Phytoplankton Chytridiomycosis: Fungal Parasites of Phytoplankton and Their Imprints on the Food Web Dynamics - SIME - NGANDO, Télesphore (Frontiers in Microbiology, 2012)
Parasitism is one of the earlier and common ecological interactions in the nature, occurring in almost all environments. Microbial parasites typically are characterized by their small size, short generation time, and high rates of reproduction, with simple life cycle occurring generally within a single host. They are diverse and ubiquitous in aquatic ecosystems, comprising viruses, prokaryotes and eukaryotes. Recently, environmental 18S-rDNA surveys of microbial eukaryotes have unveiled major infecting agents in pelagic systems, consisting primarily of the fungal order of Chytridiales (chytrids). Chytrids are considered the earlier branch of the Eumycetes and produce motile, flagellated zoospores, characterized by a small size (2-6 µm) and a single, posterior flagellum. The existence of these dispersal propagules includes chytrids within the so-called group of zoosporic fungi, which are particularly adapted to the plankton lifestyle where they infect a wide variety of hosts, including fishes, eggs, zooplankton, algae, and other aquatic fungi but primarily freshwater phytoplankton. Related ecological implications are huge because chytrids can killed their hosts, release substrates for microbial processes, and provide nutrient-rich particles as zoospores and short fragments of filamentous inedible hosts for the grazer food chain. Furthermore, based on the observation that phytoplankton chytridiomycosis preferentially impacts the larger size species, blooms of such species (e.g. filamentous cyanobacteria) may not totally represent trophic bottlenecks. Besides, chytrid epidemics represent an important driving factor in phytoplankton seasonal successions. In this review, I summarize the knowledge on the diversity, community structure, quantitative importance, and functional roles of fungal chytrids, primarily those who are parasites of phytoplankton, and infer the ecological implications and potentials for the food web dynamics and properties.